ANALISIS LAJU DOSIS SERAP MATERIAL NORM DI SEDIMEN DASAR LAUT BANDA, SULAWESI TENGAH - Ghifari Raihan Silam Siregar; Muslim Muslim; Ali Ali; Baskoro Rochaddi; Sugeng Widada; Djunaedi Muljawan; Azhar Afi (Oseanika, 2021)
[Analysis of Absorbed Dose Rate for NORM Material in Sediment of Banda Waters, Central Sulawesi] Naturally occurring radioactive materials (NORM) are materials contained in the earth and generally come from several sources such as coal burning, oil and gas production, and mining. The coastal areas of the Banda water, especially along Luwuk, Morowali, and Kendari, Central Sulawesi, are areas that become locations for several activities, such as mining, oil and gas industry, and power plants. The purpose of this study is to assess the distribution of the absorbed dose rate of NORM material in the sediment of Banda water, especially along Luwuk, Morowali, and Kendari, Central Sulawesi, and to analyze its value against existing quality standards. The absorbed dose rate of  226Ra, 232Th, dan 40K were measured at 5 stations and the results are 52.53 nGy/h; 355.75 nGy/h; 45.88 nGy/h; 131.86 nGy/h; and 35.38 nGy/h. The study shows that the distribution of the absorbed dose rate was influenced by the activities of the NORM-producing industry close to the location of the measured station. Marine current patterns and bathymetry have slight effect in this study area. The risk quotient of the absorbed dose rate is still <1 so that it indicates that the risk to organisms around the waters is still low. Keywords:      NORM, Absorbed Dose Rate, Radium, Thorium, Potassium, Banda Sea